2011
DOI: 10.1182/blood-2011-03-340992
|View full text |Cite
|
Sign up to set email alerts
|

Increase in circulating CD4+CD25+Foxp3+ T cells in patients with Philadelphia-negative chronic myeloproliferative neoplasms during treatment with IFN-α

Abstract: Recent reports have described complete or major molecular remission in patients with polycythemia vera after long-term treatment with the immunomodulatory agent IFN-␣2. Accordingly, there are reasons to believe that the immune system is a key player in eradicating the JAK2 mutated clone in these patients. Foxp3 ؉ regulatory T cells play a pivotal role in maintaining immune homeostasis and, importantly, preventing immune reactivity to self-antigens; however, their suppressive activity can compromise an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 25 publications
3
54
0
Order By: Relevance
“…Thus, we defined Tregs based on these surface markers (Fig. 4a), which we have previously demonstrated possess regulatory capacity [17]. We found significantly higher frequencies of circulating Tregs in patients with PC when compared to healthy donors (P < 0.05 Fig.…”
Section: M-mdsc Frequencies Correlate Positively To Increased Levels mentioning
confidence: 73%
“…Thus, we defined Tregs based on these surface markers (Fig. 4a), which we have previously demonstrated possess regulatory capacity [17]. We found significantly higher frequencies of circulating Tregs in patients with PC when compared to healthy donors (P < 0.05 Fig.…”
Section: M-mdsc Frequencies Correlate Positively To Increased Levels mentioning
confidence: 73%
“…Another study has confirmed the increase of Treg, enumerated in the peripheral blood by flow cytometry as CD4+ FOXP3+ CD25high cells, in patients with chronic myeloproliferative disorders, treated with peg-IFN-a2 long-term (more than 12 months) [60]. Of note, both activated (FOXP3high CD45RAlow) and cytokine-producing non-Treg (FOXP3low CD45RAlow) were expanded in that context, suggesting a double activity of IFN in promoting both effector and regulatory responses [60]. Conversely, another study has analyzed Treg frequency, as CD4+ FOXP3+ CD25high cells, in the peripheral blood of melanoma patients at very early time points (from 8 to 29 days) during IFN-a2b therapy, and found a gradual decrease in Treg percentage in most of the patients, reaching statistical significance at 4 weeks [61].…”
Section: Ifn Therapy and Treg In Ms Chc And Cancermentioning
confidence: 81%
“…In a neo-adjuvant regimen of high-dose IFN-a2b administration to melanoma patients, the percentage of FOXP3+ cells in lymphocytes was increased, in association to STAT5 upregulation, as evaluated by immunohistochemistry in biopsy specimens of regional lymph nodes, 29 days after therapy compared to pre-treatment [59]. Another study has confirmed the increase of Treg, enumerated in the peripheral blood by flow cytometry as CD4+ FOXP3+ CD25high cells, in patients with chronic myeloproliferative disorders, treated with peg-IFN-a2 long-term (more than 12 months) [60]. Of note, both activated (FOXP3high CD45RAlow) and cytokine-producing non-Treg (FOXP3low CD45RAlow) were expanded in that context, suggesting a double activity of IFN in promoting both effector and regulatory responses [60].…”
Section: Ifn Therapy and Treg In Ms Chc And Cancermentioning
confidence: 90%
“…16 There are contradictory data on numbers of Tregs in persons with PMF. [17][18][19] With the aim of determining whether Tregs were abnormal and interrogating possible associations with clinical and laboratory features, we did a cross-sectional evaluation of 202 consecutive subjects with PMF referred to the Center for the Study of Myelofibrosis, Fondazione Istituto di Ricovero e Cura a Carattere Scientifico Policlinico San Matteo of Pavia, Italy, from March 2008 to September 2015 (supplemental Methods, available on the Blood Web site). Sample size was defined by investigating blood Treg frequency in 31 subjects with PMF tested twice within 5 days.…”
mentioning
confidence: 99%